Strategies for Joint Venture Success (RLE International Business). - Killing, Peter (Routledge Library Editions: International Business., 2013)
Although published thirty years ago this book accurately predicted that joint-ventures would become an increasingly prominent feature on the corporate landscape. This book, based on the experience of managers in both successful and unsuccessful joint ventures has been written expressly to help managers improve the performance of their joint ventures. It discusses the area of joint venture design and management including the management of ventures between corporations and government bodies.